Comparative Evaluation of Antioxidative Properties and Effects of Aqueous Extracts of Cola Nitida and Vitex Doniana on Fe2+ - Generated Oxidative Stress in Rat Testes in Vitro - Saliu, Jamiyu A; Olabiyi, Ayodeji A; Adefegha, Stephen A; Oyeleye, Sunday; Olorunisola, Oluwaseun O (The International Journal of Biotechnology, 2016)
Male sexual dysfunction (MSD) might be produced by multifactorial determinants which include psychological disorders, androgen deficiencies, chronic medical conditions, vascular insufficiency, penile disease, pelvic surgery, neurological disorders, drugs, life style, aging and systemic diseases. This study sought to assess the antioxidant properties of the water-extractable component of the leaves of Black plum (Vitex doniana) and bark of Kola nut (Cola nitida),evaluate their effect on pro-oxidant generated lipid peroxidation in rat’s testes; and examine the effect on arginase which is among the major enzymes associated with Erectile dysfunction. The results of the total phenol, total flavonoid of aqueous extracts of Cola nitida and Vitex doniana revealed that Cola nitida (10.64 mgGAE/g) had significantly (P<0.05) more total phenol content than Vitex doniana (4.68 mgGAE/g). The result also revealed that Vitex doniana (2.1 mgQE/g) had significantly (P<0.05) higher total flavonoid content than Cola nitida (1.3 mgQE/g). Also, Vitex doniana (20.24 mgAEE/g) had significantly (p<0.05) higher reducing property than Cola nitida (17.43 mgAEE/g). The results of the 2, 2’-azino-bis (3-ethylbenthiazoline-6-sulphonic acid (ABTS*) radical mopping up capacity of the water extractable component of Vitex doniana and Cola nitida also showed that the extracts are able to scavenge ABTS* radicals, however, Vitex doniana (1.8 Mmol TEAC/100g) had significantly (P<0.05) higher ABTS* mopping up capability than Cola nitida (1.2 Mmol TEAC/100g). Furthermore, the DPPH* result revealed that Cola nitida and Vitex doniana extracts scavenged DPPH* radicals in a concentration-dependent pattern. However, Vitex doniana (IC50 = 1.28mg/ml) had a significantly (P<0.05) higher DPPH* mopping up capability than Cola nitida (IC50 = 0.83 mg/ml). Both extracts were able to inhibit FeSO4-generated lipid peroxidation at a dose-dependent manner; however, Vitex doniana (IC50 = 1.07 mg/ml) had a higher inhibitory action of Fe2+ induced lipid peroxidation than Cola nitida (IC50 = 1.01 mg/ml). Vitex doniana (IC50 = 0.38mg/ml) has the higher arginase inhibitory activity than Cola nitida (IC50 = 0.34mg/ml). High phenolic content and strong antioxidant properties could be part of the mechanisms through which the water extractable phytochemicals of Cola nitida (bark) and Vitex doniana (leaves) exhibits its preventive measure of erectile function. However, Vitex doniana displayed a stronger effect on Male reproductive function than Cola nitida.